Bent-Up Triangular Tab Shear Transfer (BTTST) Enhancement in Cold-Formed Steel-Concrete Composite Beams: Formulation of Design Equation - juki, mohd irwan; Ab. Hamid, Hanizah; Ibrahim, Azmi; Othman, Norzila (International Journal of Sustainable Construction Engineering and Technology, 2011)
An experimental program was conducted to study the strength and behaviour of a bent-up tabs shear transfer enhancement. Sixty eight push-out test specimens of cold-formed steel lipped channel sections (CFS) embedded in concrete plank where by usage of a new proposed shear transfer enhancement called bent-up triangular tab shear transfer (BTTST) was used in this program. This paper summarizes the results of develop an expression in order to predict the  innovative shear transfer enhancement mechanism BTTST in a new type of precast composite beam comprising Cold-formed steel (CFS) embedded in precast concrete plank. The results show that the proposed equation is in good agreement with the observed test values. The average absolute difference between the test values and predicted values was found to be 8.07%. The average arithmetic mean of the test/predicted ratio (μ) of this equation was 0.9954. The standard deviation (σ) and the coefficient of variation (CV) for the proposed equation were 0.09682 and 9.7%, respectively